Recent advances in the modeling of fundamental processes in liquid metal batteries. (April 2022) - Agarwal, Daksh; Potnuru, Rakesh; Kaushik, Chiranjeev; Darla, Vinay Rajesh; Kulkarni, Kaustubh; Garg, Ashish; Gupta, Raju Kumar; Tiwari, Naveen; Nalwa, Kanwar Singh
Abstract: Liquid Metal Batteries (LMBs) have a potential to emerge as a cost-effective solution for grid-scale energy storage to overcome the intermittency of renewable energy generation and to facilitate the management of peak loading requirements. They have significant advantages over other battery types such as high-power density and cyclability, use of earth-abundant materials, self-healing capability, high coulombic efficiency, and ease of scalability. The successful adoption of LMBs for grid storage requires a thorough understanding of the underlying processes that govern the performance of LMBs to prevent any detrimental effects at higher storage capacities. However, most of the research work in this relatively new field has focused on developing new electrode materials to achieve higher performance and lower operating temperature. In this review, we focus on other critical aspects such as heat and mass transfer, electric potential, instabilities, high temperature sealing and state of charge, which are vital to the functioning of LMBs. The models that have been developed to study these processes and attributes of LMBs, and their learning advancements have been summarized. Moreover, the challenges and outlook of research on modeling of LMBs are presented which are expected to significantly contribute to the development of a comprehensive model combining these effects that will offer insights into optimization of design and operating conditions of LMBs resulting in accelerated scaling and commercialization. Graphical abstract: Image 1